Prevalence and Antifungal Susceptibility of Candida parapsilosis Species Complex in Eastern China: A 15-Year Retrospective Study by ECIFIG - Guo, Jian; Zhang, Min; Qiao, Dan; Shen, Hui; Wang, Lili; Wang, Dongjiang; Li, Li; Liu, Yun; Lu, Huaiwei; Wang, Chun; Ding, Hui; Zhou, Shuping; et al. (Frontiers in Microbiology, 2021)
Candida parapsilosis complex is one of the most common non-albicans Candida species that cause candidemia, especially invasive candidiasis. The purpose of this study was to evaluate the antifungal susceptibilities of both colonized and invasive clinical C. parapsilosis complex isolates to 10 drugs: amphotericin (AMB), anidulafungin (AFG), caspofungin (CAS), micafungin (MFG), fluconazole (FLZ), voriconazole (VRZ), itraconazole (ITZ), posaconazole (POZ), 5-flucytosine (FCY), and isaconazole (ISA). In total, 884 C. parapsilosis species complex isolates were gathered between January 2005 and December 2020. C. parapsilosis, Candida metapsilosis, and Candida orthopsilosis accounted for 86.3, 8.1, and 5.5% of the cryptic species, respectively. The resistance/non-wild-type rate of bloodstream C. parapsilosis to the drugs was 3.5%, of C. metapsilosis to AFG and CAS was 7.7%, and of C. orthopsilosis to FLZ and VRZ was 15% and to CAS, MFG, and POZ was 5%. The geometric mean (GM) minimum inhibitory concentrations (MICs) of non-bloodstream C. parapsilosis for CAS (0.555 mg/L), MFG (0.853 mg/L), FLZ (0.816 mg/L), VRZ (0.017 mg/L), ITZ (0.076 mg/L), and POZ (0.042 mg/L) were significantly higher than those of bloodstream C. parapsilosis, for which the GM MICs were 0.464, 0.745, 0.704, 0.015, 0.061, and 0.033 mg/L, respectively (P < 0.05). The MIC distribution of the bloodstream C. parapsilosis strains collected from 2019 to 2020 for VRZ, POZ, and ITZ were 0.018, 0.040, and 0.073 mg/L, significantly higher than those from 2005 to 2018, which were 0.013, 0.028, and 0.052 mg/L (P < 0.05). Additionally, MIC distributions of C. parapsilosis with FLZ and the distributions of C. orthopsilosis with ITZ and POZ might be higher than those in Clinical and Laboratory Standards Institute studies. Furthermore, a total of 143 C. parapsilosis complex isolates showed great susceptibility to ISA. Overall, antifungal treatment of the non-bloodstream C. parapsilosis complex isolates should be managed and improved. The clinicians are suggested to pay more attention on azoles usage for the C. parapsilosis complex isolates. In addition, establishing the epidemiological cutoff values (ECVs) for azoles used in Eastern China may offer better guidance for clinical treatments. Although ISA acts on the same target as other azoles, it may be used as an alternative therapy for cases caused by FLZ- or VRZ-resistant C. parapsilosis complex strains.